Youth negotiation of citizenship identities in Pakistan: Implications for global citizenship education in conflict-contexts. Issue 4 (2nd October 2018) - Kadiwal, Laila; Durrani, Naureen
ABSTRACT: This study explores young students' negotiation of their citizenship identities at the intersection of their class, gender, religious and ethnic identifications in the conflict-affected setting of Pakistan. While much of the global literature on global citizenship education (GCE) primarily takes into account the perspectives of middle-class or elite students located in richer economies, the current study is centred on a socio-demographically diverse group of young people in a low-income setting. With a specific focus on their negotiation of issues around diversity and justice, students' narratives generated important recommendations for a transformative and historically nuanced postcolonial/decolonial approach to global citizenship engagement that should be considered more broadly. The study illuminates the ways the global/local historical, cultural, political and economic factors influence individual relationship with GCE and offers useful pedagogical and policy implications for GCE 'from below'.